The Role of Alpha Linolenic Acid on Neuroinflammation: A Systemic Review - Wijaya, Debby Chesilya; Linawati, Ni Made (Jurnal Penelitian Pendidikan IPA, 2024)
Neuroinflammation, an inflammatory response within the central nervous system (CNS), plays a critical role in various neurological disorders, including neurodegenerative diseases. Alpha linolenic acid (ALA), an essential omega-3 polyunsaturated fatty acid, has shown promising health benefits due to its antioxidant and anti-inflammatory properties. This article aims to thoroughly examine the potential effects of ALA in reducing neuroinflammation, emphasizing its roles as an anti-inflammatory and antioxidant agent. The review focuses on studies published between 2018 and 2023, sourced from reputable academic databases such as PubMed, Semantic Scholar, Google Scholar, and ScienceDirect, with nine key papers selected. The findings indicate that ALA significantly mitigates neuroinflammation by decreasing reactive oxygen species (ROS) via the Nrf-2/HO-1/JNK signaling pathway. Additionally, ALA reduces inflammatory cytokines by inhibiting p-JNK activation, disrupting lipid rafts, blocking the pro-inflammatory transcription factor NF-κB, and altering cell membrane phospholipid composition. The review concludes that ALA may have potential therapeutic effects in reducing neuroinflammation through its antioxidant and anti-inflammatory actions, offering possible benefits for various neurological conditions, including Alzheimer's and Parkinson's diseases.